Do Digital Competence and Learning Culture Drive Agility and Innovation Capability through Knowledge Sharing? - Fildansyah, Rully; Nailul, Muhammad (Westscience Press, 2025)
This study examines the impact of digital competence and learning culture on organizational agility and innovation through the mediating role of knowledge sharing in Indonesia. Utilizing a quantitative approach, data were collected from 100 respondents across diverse industries using a structured questionnaire measured on a 5-point Likert scale. Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) was employed to analyze the relationships between the variables. The results reveal that both digital competence and learning culture have a significant positive effect on knowledge sharing. In turn, knowledge sharing significantly influences both agility and innovation. Furthermore, knowledge sharing mediates the effects of digital competence on agility and of learning culture on innovation. These findings underscore the strategic importance of fostering digital capabilities and a learning-oriented culture to drive knowledge-based organizational performance in the context of Indonesia’s digital transformation.